Basic elements of sponsorship contract in sport - Jagodic, Tone (Array, 2018)
Sponsorship represents very important source of finances for many sports organizations. The aim of the article is to analyze structural elements of sponsorship contract and to propose a proper definition of a sponsorship contract, while leaning on the many sources of comparative law. The review of foreign legislation shows that not one country has yet legally enacted the sponsorship contract. Some legislation regulate sponsorship in an indirect way using common rules of contractual law or some elements of other contracts, which are already well known and regulated by legal systems. In determining the validity of the arguments cited by the individual authors in the literature our aim is to come to some conclusions which have been summarized in following parts of this article. It seems that the Code of sponsorship of the International Chambers of Commerce (ICC) gives the real foundation which can be useful for different sport organizations. Following the ICC International Code on Sponsorship, the definition of a sponsorship agreement “is any commercial agreement by which a sponsor, for the mutual benefit of the sponsor and a sponsored party, contractually provides financing or other support in order to establish an association between the sponsor’s image, brands or products and a sponsorship property in return for the rights to promote this association and/or for the granting of certain agreed direct or indirect benefits.” Brand of the sponsor, identification with the property of the sponsored subject, commercial agreement, right to promote and mutual benefit are the vital components of a sponsorship contract which are contained in the ICC definition. We also believe that in the future, this definition could lead to the right definition for a possible codification of a sponsorship contract on the national level.